Pola Asuh Orang Tua dalam Keluarga Pernikahan Dini dan Pengaruhnya terhadap Perkembangan Sosial Anak Usia Dini di Desa Mulyorejo - Aryanti, Aryanti; Amilda, Amilda; Atika, Nyimas (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to describe parenting patterns in families with early marriages and analyze their influence on the social development of early childhood in Mulyorejo Village. The focus of the study is on how parenting practices are applied by parents who married at a young age, and how these patterns shape children's social behavior, interaction skills, and self-adjustment in their peer environment. This study uses a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results show that early marriage families apply three main parenting styles, namely authoritarian, permissive, and democratic, each of which has a different impact on social development. Democratic parenting tends to produce children who are independent, communicative, and able to interact positively; authoritarian parenting is associated with closed-mindedness, low self-esteem, and passivity in socializing; while permissive parenting influences a lack of self-control and understanding of social boundaries. This study recommends improving parenting education for parents of early marriages, especially regarding democratic parenting, which better supports the optimal social development of young children